Roman imperial armour - Sim, David (Oxbow Books, 2012)
The Roman Empire depended on the power of its armies to defend and extend the imperial borders, enabling it to dominate much of Europe, Northern Africa and the Middle East. Success was, in large part, founded on well-trained, well-disciplined soldiers who were equipped with the most advanced arms and armour available at that time. This is the story of the production of that armour. Roman Imperial Armour presents an examination of the metals the armour was made from, of how the ores containing those metals were extracted from the earth and transformed into workable metal and of how that raw pro